2014
DOI: 10.1371/journal.pone.0104972
|View full text |Cite
|
Sign up to set email alerts
|

Regional Variation in Tissue Composition and Biomechanical Properties of Postmenopausal Ovine and Human Vagina

Abstract: ObjectiveThere are increasing numbers of reports describing human vaginal tissue composition in women with and without pelvic organ prolapse with conflicting results. The aim of this study was to compare ovine and human posterior vaginal tissue in terms of histological and biochemical tissue composition and to assess passive biomechanical properties of ovine vagina to further characterise this animal model for pelvic organ prolapse research.Study DesignVaginal tissue was collected from ovariectomised sheep (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 25 publications
(36 reference statements)
2
21
0
Order By: Relevance
“…However, we did not find studies describing physiological changes during the lifespan of asymptomatic women. We came across one study comparing the collagen ratio and total collagen content in the vaginal wall of castrated sheep being compared to that of menopausal women -yet without comparable measurements in premenopausal subjects [12]. This is a comparison we cannot make.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, we did not find studies describing physiological changes during the lifespan of asymptomatic women. We came across one study comparing the collagen ratio and total collagen content in the vaginal wall of castrated sheep being compared to that of menopausal women -yet without comparable measurements in premenopausal subjects [12]. This is a comparison we cannot make.…”
Section: Discussionmentioning
confidence: 99%
“…Non-human primates are closest to humans [7][8][9], however, their use in research has been nearly completely banned in Europe [10]. Sheep may be alternatives as their pelvic floor anatomy and dimensions as well as the microscopic architecture have many similarities to that of humans [11,12]. We and others have recently become interested in sheep for pelvic floor research and experimental surgery [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vaginal tissue is anisotropic1940, thus biaxial testing is currently the most equivalent test available. It is superior to uniaxial biomechanical testing as this only measures properties in one direction, which does not represent the physiologic environment, in which strain is placed on the vaginal wall in all directions182641.…”
Section: Discussionmentioning
confidence: 99%
“…Due to narrowing of the ewe vagina at the apical end, the 4 cm × 4 cm tissue required for biomechanical testing was taken from the mid-region of the posterior wall. Previous studies have demonstrated similarity in the biochemical and biomechanical properties of the lower-and-mid regions of the ovine vaginal wall41. To avoid the hymnal ring, tissue adjacent to the piece for biomechanical analysis was excised and fixed in 10% formalin, paraffin embedded and 5 μm sections were stained with Haemotoxylin and Eosin (H&E), Masson’s Trichrome and Hart’s elastic fibre stain in the Monash Histology Platform (MHP) facility.…”
Section: Methodsmentioning
confidence: 99%